Game-based learning approach in computer science in primary education: A systematic review - Videnovik, Maja; Madevska Bogdanova, Ana; Trajkovikj, Vladimir (Elsevier, 2024)
This paper reviews the current situation concerning the implementation of game-based learning in computer science in primary education, providing insight into current trends, identifying strengths and potential research topics. Articles published in four databases from 2017 to 2021 are included in the analysis and an in-depth analysis of 32 articles is done. Different types of games, implemented in various educational contexts, are presented in these articles. Most of them describe implemented methodology, game-based environment or are evaluating the effectiveness of the created game or the approach. The possibility of implementing a game-based approach while learning other computer science topics or measuring the effectiveness of learning by designing a game as a pedagogical strategy are some areas for future research.